Inducing Effect of Diamines on Transcription of the Cephamycin C Genes from the lat and pcbAB Promoters in Nocardia lactamdurans - Leitão, Ana Lucia (American Society for Microbiology, 1999)
The diamines putrescine, cadaverine, and diaminopropane stimulate cephamycin biosynthesis in Nocardia lactamdurans, in shake flasks and fermentors, without altering cell growth. Intracellular levels of the P7 protein (a component of the methoxylation system involved in cephamycin biosynthesis) were increased by diaminopropane, as shown by immunoblotting studies. Lysine-6-aminotransferase and piperideine-6-carboxylate dehydrogenase activities involved in biosynthesis of the α-aminoadipic acid precursor were also greatly stimulated. The diamine stimulatory effect is exerted at the transcriptional level, as shown by low-resolution S1 protection studies. The transcript corresponding to the pcbAB gene and to a lesser extent also the lat transcript were significantly increased in diaminopropane-supplemented cultures, whereas transcription from the cefD promoter was not affected. Coupling of the lat and pcbAB promoters to the reporter xylE gene showed that expression from the lat and pcbAB promoters was increased by addition of diaminopropane in Streptomyces lividans. Intracellular accumulation of diamines in Nocardia may be a signal to trigger antibiotic production.